Al-ʿAnāṣir as-Sulūkiyyah fī aṭ-Ṭarīqah as-Samʿiyyah asy-Syafawiyyah fī Taʿlīm al-Lughah aṯ-Ṯāniyyah - Alif Cahya Setiyadi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
Behaviorism is one of the major theories in psychology that focuses on observable human behavior. One of the principal characteristics of the behaviorist theory of learning is the central role of the teacher in transmitting knowledge to learners, together with its firm emphasis on the conditioning of linguistic behavior through operant conditioning and stimulus-response associations. Based on these characteristics, behaviorist theory gave rise to behaviorist approaches and teaching methods. The application of behaviorist theory was later extended to become a theory of language learning and language teaching. Among the instructional methods derived from this theory are the Direct Method and the Audio-Lingual Method. The Audio-Lingual Method contains a number of behavioral elements that every language teacher should possess and apply effectively. Through this study, the researchers attempt to identify and explain these behavioral elements in a comprehensive and systematic manner.